Macroinfauna responses and recovery trajectories after an oil spill differ from those following saltmarsh restoration. (March 2020) - Fleeger, J.W.; Johnson, D.S.; Zengel, S.; Mendelssohn, I.A.; Deis, D.R.; Graham, S.A.; Lin, Q.; Christman, M.C.; Riggio, M.R.; Pant, M.
Abstract: Given the severity of injuries to biota in coastal wetlands from the Deepwater Horizon oil spill ( DWH ) and the resulting availability of funding for restoration, information on impacted salt marshes and biotic development of restored marshes may both help inform marsh restoration planning in the near term and for future spills. Accordingly, we performed a meta-analysis to model a restoration trajectory of total macroinfauna density in constructed marshes (studied for 30 y), and with a previously published restoration trajectory for amphipods, we compared these to recovery curves for total macroinfauna and amphipods from DWH impacted marshes (over 8.5 y). Total macroinfauna and amphipod densities in constructed marshes did not consistently reach equivalency with reference sites before 20 y, yet in heavily oiled marshes recovery occurred by 4.5 y post spill (although it is unlikely that macroinfaunal community composition fully recovered). These differences were probably due to initial conditions (e.g., higher initial levels of belowground organic matter in oiled marshes) that were more conducive to recovery as compared to constructed marshes. Furthermore, we found that amphipod trajectories were distinctly different in constructed and oiled marshes as densities at oiled sites exceeded that of reference sites by as much as 20x during much of the recovery period. Amphipods may have responded to the rapid increase and high biomass of benthic microalgae following the spill. These results indicate that biotic responses after an oil spill may be quantitatively different than those following restoration, even for heavily oiled marshes that were initially denuded of vegetation. Our dual trajectories for oil spill recovery and restoration development for macroinfauna should help guide restoration planning and assessment following the DWH as well as for restoration scaling for future spills. Highlights: Macroinfauna density in restored salt marshes is slow to mature, >20 y. Macroinfauna density recovery from the Deepwater Horizon oil spill was much faster, 4.5 y. Densities were higher in heavily oiled marshes than references, 3–8 y post spill. Improving initial soil quality and vegetation cover should aid restoration success. These recovery trajectories may guide future restoration planning and assessment.